2013
DOI: 10.1071/cp13201
|View full text |Cite
|
Sign up to set email alerts
|

Yield components of maize as affected by short shading periods and thinning

Abstract: Maize (Zea mays) grain yield has been described to be particularly susceptible to environmental conditions around silking; however, a better temporal description of the effect of resource deprivation during this period is needed. Additionally, yield progress and the subsequent increase in the demand of assimilates may result in source limitation during the grain-filling period in current hybrids. This work assessed the effect of (i) short (~5 days) and intense shading stresses imposed at different times, and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(30 citation statements)
references
References 33 publications
0
28
0
2
Order By: Relevance
“…The negative post-silking dry matter accumulation of ZD958, JY877 and SY29 in 2016 was possibly because of leaf and stem rotting caused by intermittent rainfall during grain filling. The reduced post-silking dry matter accumulation may be due to the decreased photosynthetic capacity attributed to light deprivation, which limits the source capacity for grain development [5,6,8,11]. The low SPAD value and photosynthetic rate (unpublished data) under shading indicated that the photosynthetic function deteriorated, and the leaf photoprotection mechanism was probably damaged, thereby decreasing photosynthesis and dry matter accumulation [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative post-silking dry matter accumulation of ZD958, JY877 and SY29 in 2016 was possibly because of leaf and stem rotting caused by intermittent rainfall during grain filling. The reduced post-silking dry matter accumulation may be due to the decreased photosynthetic capacity attributed to light deprivation, which limits the source capacity for grain development [5,6,8,11]. The low SPAD value and photosynthetic rate (unpublished data) under shading indicated that the photosynthetic function deteriorated, and the leaf photoprotection mechanism was probably damaged, thereby decreasing photosynthesis and dry matter accumulation [10].…”
Section: Discussionmentioning
confidence: 99%
“…Shading at the flowering stage inhibits photosynthesis and diminishes kernel size, weight, glucose and starch contents [5]. Post-silking shading reduces the number of maize grains because of a limited source capacity [6], and a decreased kernel set is primarily in apical ear regions because of the decreased photosynthesis, the increased abscisic acid level and the nearly halted accumulation of nonstructural carbohydrate [7]. Plants suffering from a low sunlight intensity at the post-silking stage experience a dissolution of their cell membrane, karyotheca, mitochondria and some membrane structures, leading to a decreased photosynthetic capacity [8].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, both grain number and grain weight are affected by the amount of assimilates available per floret and/or grain during the critical period for grain number determination (Calderini et al, 1999b;Gambín et al, 2006;Ugarte et al, 2007;Borrás and Gambín, 2010;Ferrise et al, 2010;Hasan et al, 2011;Ferrante et al, 2012). However, if the crop goes through limitations in assimilate availability during the effective grain-filling period (e.g., reduced incoming solar radiation or accelerated senescence), the potential would not be realized, presumably due to source limitation during grain filling (Cerrudo et al, 2013). For instance, artificial manipulations to reduce fruiting efficiency (the efficiency of converting plant growth around flowering into grains) by reducing the number of florets setting grains but not altering growth and partitioning around flowering, resulting in final grain size increases in both wheat (Triticum aestivum L.) (Calderini and Reynolds, 2000) and maize (Gambín et al, 2006).…”
Section: Maize Grain Weight Sensitivity To Source-sink Manipulationsmentioning
confidence: 99%
“…In maize, it is frequently accepted that the potential grain size is achieved if the crop does not go through "major limitations" in assimilate availability (Borrás and Westgate, 2006), and then grain growth would be sink limited during this period Maddonni et al, 1998;Gambín et al, 2008). However, if the crop goes through limitations in assimilate availability during the effective grain-filling period (e.g., reduced incoming solar radiation or accelerated senescence), the potential would not be realized, presumably due to source limitation during grain filling (Cerrudo et al, 2013). The controversies are supported by the statement raised long ago by Tollenaar and Daynard (1982), who pointed out that "a delicate balance exists between sink and source during the grainfilling period of maize and that disturbance of this balance can cause substantial yield reductions."…”
Section: Maize Grain Weight Sensitivity To Source-sink Manipulationsmentioning
confidence: 99%
“…Heat waves can potentially affect yield during reproductive growth by reducing the amount of time that male (tasseling) and female (silking) flowering periods overlap (Bolaños and Edmeades, 1996;Cantarero et al, 1999) or by decreasing reproductive tissue viability. Increased temperatures affect tissue viability by slowing transfer of photosynthate to the ear during ovule fertilization (Suwa et al, 2010), leading to lower kernel sugar content and greater kernel abortion rates (Cerrudo et al, 2013;Hiyane et al, 2010). Additionally, exposure to temperatures above 32 o C can decrease pollen viability (Herrero and Johnson, 1980).…”
Section: Introductionmentioning
confidence: 99%